2015
DOI: 10.3102/0013189x15591157
|View full text |Cite
|
Sign up to set email alerts
|

Minorities Are Disproportionately Underrepresented in Special Education

Abstract: We investigated whether and to what extent minority children attending elementary and middle schools in the U.S. are over- or under-identified as disabled and so disproportionately represented in special education. To address existing limitations in the field's knowledge base, we (a) analyzed multi-year longitudinal data, (b) used hazard modeling to estimate over-time dynamics of disability identification across five specific conditions, and (c) extensively corrected for child-, family-, and school-level poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
315
3
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(352 citation statements)
references
References 88 publications
21
315
3
6
Order By: Relevance
“…Research has consistently shown persistent underachievement to be the strongest predictor of specialized needs in school (Morgan et al, ). Other literature has indicated race, socioeconomic status (SES; e.g., Donovan & Cross, ; Morgan et al, ), and sex (e.g., Coutinho & Oswald, ; Hibel, Farkas, & Morgan, ) are associated with risk of identification, though the conclusions drawn from these studies have been mixed. Some researchers have found nonsignificant effects of SES after controlling for other child and school‐level factors (Kincaid & Sullivan, ; Skiba, Poloni‐Staudinger, Simmons, Renae feggins‐Azziz, & Chung, ), whereas others primarily attribute over representation of Black children in special education to the disadvantages of poverty (Morgan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has consistently shown persistent underachievement to be the strongest predictor of specialized needs in school (Morgan et al, ). Other literature has indicated race, socioeconomic status (SES; e.g., Donovan & Cross, ; Morgan et al, ), and sex (e.g., Coutinho & Oswald, ; Hibel, Farkas, & Morgan, ) are associated with risk of identification, though the conclusions drawn from these studies have been mixed. Some researchers have found nonsignificant effects of SES after controlling for other child and school‐level factors (Kincaid & Sullivan, ; Skiba, Poloni‐Staudinger, Simmons, Renae feggins‐Azziz, & Chung, ), whereas others primarily attribute over representation of Black children in special education to the disadvantages of poverty (Morgan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…National and state-level data also indicate that ASD is the fastest growing developmental disability, resulting in long waits to obtain services (Boyle et al, 2011; Jones et al, 2016; Michigan ASD State Plan, 2012). Past research has demonstrated that a decreased awareness of ASD symptomatology can lead to underreporting and resistance to obtaining diagnostic labels for their grandchildren, which then contributes to the longer time from onset to diagnosis among African American children than among Caucasian children (Burkett et al, 2015; Jarquin et al, 2011; Morgan et al, 2015; Ratto et al, 2016). Timely recognition of a grandchild’s health problems is the first step in obtaining supportive services such as occupational therapy to improve the functional outcomes of grandchildren who may be at risk for developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic screening of grandchildren at risk for poor developmental outcomes can enable follow-up efforts that include timely referrals of children for supportive interventions, thereby ameliorating the racial disparities within the U.S. special education system (Morgan et al, 2015; Morgan & Farkas, 2016). The effect of grandparent health on grandchild caregiving and family quality of life also deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the United States, students who are categorized as cognitively, emotionally, behaviorally, and/or physically disabled qualify for supplemental, individualized educational services under the federal Individuals with Disability Education Act. Although questions persist regarding these resources’ consequences and the role they play in practice (see Shifrer et al 2013), their intent is to provide a better educational experience than these students would otherwise experience (Morgan et al 2015). …”
Section: From Categories To Categorical Inequalitiesmentioning
confidence: 99%